Two Events with Spectacular Moving Structures in a Failed Solar Filament Eruption - Yudi Ou; Yingna Su; Qingmin Zhang; Haisheng Ji; Leping Li; Hongqiang Song; Yijun Hou; Guiping Zhou; Baolin Tan; Kaifan Ji; Zhe Xu; Yongyuan Xiang; et al. (The Astrophysical Journal, 2025)
We investigate the complex magnetic reconnection process between the filament and surrounding loops during the failed filament eruption that occurred in NOAA active region 13445 on 2023 September 24, using extreme-ultraviolet observations from the Solar Dynamics Observatory and high-resolution H α imaging from the New Vacuum Solar Telescope. This failed filament eruption is associated with an M4.4 flare (SOL2023-09-24T03:28). At the early phase of the filament eruption, the filament displays a distinct clockwise rotational motion, suggesting an untwisting motion. During the flare precursor phase, the northwest slipping motion of the brightenings at the filament’s left footpoint, along with the brightening and continuous expansion of the nearby loops at the northwest, suggest the occurrence of a slipping magnetic reconnection between the filament and peripheral loops at the quasi-separatrix layer. After the slipping motion begins, significant brightenings of filament materials and multiple bright structures moving toward the two filament footpoints are observed during the two episodes of magnetic reconnection between the filament and the overlying loops, with the most prominent brightenings and the moving structures occurring during the main phase of the M4.4 flare. The observed untwisting motion of the filament and the twist reduction derived from the nonlinear force-free field extrapolation suggest that the magnetic reconnection between the filament and the peripheral and overlying loops plays a significant role in the failure of the filament eruption by greatly reducing its twist.